Semantic and Linguocultural Features of Proverbs in the Korean and Uzbek Languages: A Comparative Analysis - Kholmirzayev, Abdulaziz Bekmirza ugli (The Lingua Spectrum, 2026)
This article provides a comparative analysis of the semantic and linguocultural features of selected Korean proverbs and their meaningful counterparts in Uzbek. The study focuses on the following Korean proverbs: 가재는 게 편, 가지 많은 나무에 바람 잘 날 없다, 같은 값이면 다홍치마, 개구리 올챙이 적 생각 못한다, 고래 싸움에 새우 등 터진다. The research employs semantic, comparative, and linguocultural analysis methods. It examines the lexical composition of the proverbs, their literal and figurative meanings, imagery, and the national and cultural concepts expressed through these linguistic units. Particular attention is given to comparing the images used in Korean and Uzbek to express identical or similar life situations and identifying their common and distinctive features. The findings demonstrate that Korean and Uzbek proverbs share common semantic meanings related to human experience, moral values, and social relationships. However, the ways in which these meanings are expressed are closely connected with the national worldview, historical experience, lifestyle, and cultural characteristics of each nation. The results also highlight the linguocultural and communicative value of using proverbs in Korean language teaching.